A practical analytical model for performance prediction in unconventional gas reservoir - Qiu, Kaixuan (Frontiers in Earth Science, 2023)
90% of newly proven natural gas reservoirs of China are mainly unconventional resources, which can be typically developed by multi-stage fracturing horizontal well technology. Two regions typically occur near each fracture after hydraulic fracturing, in which the lower permeability region is considered as the storage source and the higher permeability region as the flow channel. The existed analytical models so far are mainly derived by Laplace transforming. In this paper, an improved practical analytical solution is derived for unconventional gas reservoirs bypassing the Laplace transform and numerical inversion. Through solving material balance equation and adopting the integration, a rate vs. pseudo-time solution in real-time domain can be directly obtained. Five numerical cases are created to verify the accuracy of the proposed analytical solution and the ratio of regular/irregular region pore volume is also proved to be derived reversely by the output parameters, which is significant for the field engineers to evaluate the effect of hydraulic fracturing. Moreover, a field example of a multi-fractured horizontal well in a tight gas reservoir is provided for demonstrate application.